Utilization of health care services before and after media attention about fatal side effects of the AstraZeneca vaccine: a nation-wide register-based event study - Vilde Bergstad Larsen; Mari Grøsland; Kjetil Telle; Karin Magnusson (BMC, 2021)
Abstract Background Survey studies have found that vaccinated persons tend to report more side effects after being given information about side effects rather than benefits. However, the impact of high media attention about vaccine-related side effects on the utilization of health care is unknown. We aimed to assess whether utilization of health care services for newly vaccinated health care workers changed after media attention about fatal side effects of the AstraZeneca vaccine on March 11th, 2021, and whether changes differed by age, sex, or occupation. Methods We utilized individual-level data on health care use, vaccination, employment, and demographics available in the Norwegian emergency preparedness register Beredt C19. In all 99,899 health care workers in Norway who were vaccinated with AstraZeneca between February 11th and March 11th, we used an event-study design with a matched comparison group to compare the change in primary and inpatient specialist care use from 14 days before to 14 days after the information shock on March 11th, 2021. Results Primary health care use increased with 8.2 daily consultations per 1000 health care workers (95% CI 7.51 to 8.89) the week following March 11th for those vaccinated with AstraZeneca (n = 99,899), compared with no increase for the unvaccinated comparison group (n = 186,885). Utilization of inpatient care also increased with 0.8 daily hospitalizations per 1000 health care workers (95% CI 0.37 to 1.23) in week two after March 11th. The sharpest increase in daily primary health care use in the first week after March 11th was found for women aged 18-44 (10.6 consultations per 1000, 95% CI 9.52 to 11.68) and for cleaners working in the health care sector (9.8 consultations per 1000, 95% CI 3.41 to 16.19). Conclusions Health care use was higher after the media reports of a few cases of fatal or severe side effects of the AstraZeneca vaccine. Our results suggest that the reports did not only lead vaccinated individuals to contact primary health care more, but also that physicians referred and treated more cases to specialist care after the new information.